Risk assessment for detritus flow in the city of Calca - Cusco (2018) - Maldonado Leiva, Frank Omar (2019)
The present document shows the result from the study “Risk Assessment for Detritus flow in the City of Calca- Cusco (2018)”, elaborated before the possibility of occurrence from this natural phenomenon, with the purpose of proposing control measures that lead to reduce the risk of a disaster in this city. The study is made according to the methodological requirements established by the National Center for Disaster Risk Estimation, Prevention and Reduction. (CENEPRED).